Sara J. Brenneis. Genre Fusion: A New Approach to History, Fiction, and Memory in Contemporary Spain. West Lafayette, Indiana: Purdue UP, 2014. viii + 241 pp. - Anna E Hiller (Studies in 20th & 21st Century Literature, 2015)
Review of Sara J. Brenneis. Genre Fusion: A New Approach to History, Fiction, and Memory in Contemporary Spain. West Lafayette, Indiana: Purdue UP, 2014. viii + 241 pp.
Keywords: Spanish Literature; Spanish Civil War; 20th Century Literature; dictatorship; postwar; Transition; genre; history; narrative; collective memory